Willingness to pay for residential PV: Reconciling gaps between acceptance and adoption - Phuong M. Khuong; Fabian Scheller; Russell McKenna; Dogan Keles; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2020)
Photovoltaic (PV) has recorded an impressive development in the last years. The increasing economic potential and further technological improvement will continue to reduce the cost of PV. However, it is not yet well adopted by household customers. Adversely, there is lacking empirical evidence for understanding residential PV adoption behaviour, which this study addresses with empirical research. Although a variety of models can be used to explain social acceptance (SA) and willingness to pay (WTP) for renewable energy, they overlook the connection between SA and WTP in the final purchase decision of a decision-maker. Based on a survey of both SA and WTP in the same observation sample of 2039 Vietnamese residents, this study introduces well-established models with a new linking psychological and economic aspects to measure multiple outcomes involving residential PV behaviours to testing hypotheses with no precedent in the literature. The theoretical and integrative moderated mediation models help to understand residential PV behaviour and suggest solutions for development by revealing how different factors affect SA and WTP in different manners. Environmental interest reveals the predictive power within the SA and WTP behaviour models. Meanwhile, PV knowledge drives SA, but not WTP in Vietnam. Attitude and Perceived behavioural control not only impact SA and WTP directly but also mediate the effect of Environmental interest and SA and WTP. Age & Marital status & Children and Place of residence are important covariates that drive in the SA and WTP models, respectively. Lastly, Income is the covariate in the SA model, but the moderator in the WTP model. In practical implications, this study provides evidence that residential PV is a lifestyle product rather than an economical product, but it is not considered as an essential good for household customers. Thereby, suggestions are given to policymakers and stakeholders to promote market development.
Keywords: 330; Developing country; Willingness to pay; Social acceptance; Residential photovoltaic